The Effectiveness of Static and Dynamic Balance Training on Passing Accuracy Among 15–16-Year-Old Players at Bassura Muda Futsal Academy - Muhammad Iqbal Darwis (Journal of Health and Recreation Physical Education (JHRPE), 2026)
This study aims to determine: (1) the effectiveness of static balance training in improving passing accuracy of Bassura Muda Futsal School players aged 15-16 years, (2) the effectiveness of dynamic balance training in improving passing accuracy of Bassura Muda Futsal School players aged 15-16 years, and (3) the difference in effectiveness between static balance training and dynamic balance training on passing accuracy of Bassura Muda Futsal School players aged 15-16 years. The research method used was an experiment with a two group pretest-posttest design. The research sample consisted of 30 players divided into two groups, namely the static balance training group and the dynamic balance training group, each consisting of 15 players. The research instrument used was a passing accuracy test (Four Box Pass). Data analysis used the Shapiro-Wilk normality test, Levene's Test homogeneity test, Wilcoxon Signed Rank Test, and Mann-Whitney U Test with a significance level of 0.05. The results of the study showed that: (1) static balance training is effective in improving passing accuracy, evidenced by the Asymp. Sig. value. (2-tailed) of 0.002 < 0.05; (2) dynamic balance training is also effective in improving passing accuracy, as evidenced by the Asymp. Sig. (2 tailed) value of 0.001 < 0.05; and (3) the Mann-Whitney U Test results showed a significance value of 0.069 > 0.05, indicating no significant difference in effectiveness between static balance training and dynamic balance training in improving passing accuracy. Thus, both exercises are equally effective in improving passing accuracy for Bassura Muda Futsal School players aged 15-16 years, but do not statistically show a significant difference in effectiveness